PENGARUH DISIPLIN KERJA DAN MOTIVASI KERJA TERHADAP KINERJA KARYAWAN (STUDI KASUS PADA BANK BJB CABANG KARAWANG) - Ilham Maulana Irianto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study aims to examine and analyze the Effect of Work Discipline and Work Motivation on Employee Performance (Case Study at Bank BJB Karawang Branch). This research was conducted using descriptive and verification methods, namely: collecting, presenting, analyzing and testing hypotheses, as well as making conclusions and suggestions. Sampling was carried out by the Slovin method and the Stratified SampIing technique. so that obtained a sample of 107 respondents. The analytical technique used is a Likert scale analysis technique and path analysis with the tools Method Of Successive Interval (MSI), Microsoft Office, and SPSS version 20. Based on the results of the analysis that has been carried out this study proves that Work Discipline shows an average value of 386.3 the criteria agree, work motivation shows an average value of 388.8 with the criteria agree, and employee performance shows an average value of 383.8 with the criteria agree. The correlation between Work Discipline and Work Motivation is 0.782 with a strong relationship level, Partial Effect of Work Discipline on Employee Performance is 47.1%, Work Motivation is 43.5%. Simultaneous effect of 73% while the remaining 27% is the contribution of other variables not examined.